Gênese e levantamento de solos da Serra de Santana no Seridó Potiguar - Farias, Phamella Kalliny Pereira (2016)
In understanding a more appropriate management, the soil survey in a region it has a fundamental importance. Thus, a constant updating of the soil classes is necessary for the various agricultural uses are analyzed and established the most appropriate way possible. The Rio Grande do Norte has hills formations that differ from the soil and climatic conditions prevailing in the state, with deeper soils and acidic and milder weather. Among these formations, there is the Santana’s Hill, which is embedded in the Martins Formation with deposits settled in disagreement over the lens and inserted basis in the Potiguar Seridó region, with important agricultural use for the region, with mainly cashew cultivation and cassava. With this, the objective of this study was to understand the genesis of representative soils of the Santana’s Hill and draw up an exploratory soil map of the region. Morphological, physical, chemical and mineralogical analyzes of representative profiles were performed that make up the Santana’s Hill. Representative profiles were classified as Typic Haplustox; Xanthic Eutrustox; Typic Eutrustox; Ustic Quartzipsamments; Lithic Ustorthents; Typic Ustipsamments and Dystric Haplustepts. By observing morphological attributes it was noticed that there was a great influence of the parent material factor in distinguishing the main soil types found in the study area, since the topography and climatic conditions are similar throughout the territorial extension. The textural class of the profiles studied ranged from sandy to sandy-clay-sandy due to high existing levels in sand horizons, identifying minerals that were more resistant to weathering process and the strong link with the material of sedimentary origin. All profiles showed acid reaction, wide range of base saturation between profiles and low values of electrical conductivity. The mineralogical composition of the clay fraction of the profiles were similar, with clay type Illite/Mica, Kaolinite and Goethite, and Quartz peaks. The use of GIS allows updating existing soil classes in the Santana’s Hill, as well as updating the percentage of occupation of each soil type